Is Pomegranate juice has a vital role for protective effect on Saccharomyces cerevisiae growth? - Aslan, Abdullah; Baspinar, Serpil; Yilmaz, Okkes (Mattioli 1885, 2014)
In this study, four groups were composed. i: Control group, ii: H2O2 group, iii: Pomegranate juice (PJ) group and iv: PJ + H2O2 group. After sterilization, pj (20%) and H2O2 (6% v/v) were inserted to Saccharomyces cerevisiae (S. cerevisiae) cultures and the cultures were developed at 60 degrees C for 1h, 2h, 4h and 72 hours (overnight). Fatty acids and vitamin values were gauged by HPLC and GC, the total protein was determined by SDS- PAGE. with respect to our studies results; fatty acid synthesis rised in groups to which PJ was taken in proportion to the control group (p< 0,05). Vitamin ingredient also rised particularly in the group to which PJ was taken in proportion to the control (p< 0,05). In addition, cell intensity was gauged to be upward of in PJ groups in proportion to the control (p< 0,05), whereas banding was observed more in PJ groups in proportion to the control. As a result PJ has a protective role for decrease the oxidative damage in S. cerevisiae.
Keywords: S. cerevisiae; Pomegranate juice; oxidative damage; SDS-PAGE